2021
DOI: 10.14505//jemt.v12.2(50).03
|View full text |Cite
|
Sign up to set email alerts
|

Development of the Organizational and Economic Mechanisms of Greenhouse Industry in the Republic of Uzbekistan

Abstract: The goal of the article is to analyse the improvement of the organizational and economic mechanisms of the glasshouse industry in the Republic of Uzbekistan. The following methods were used in the study: comparative analysis, statistical method, estimation method, economic analysis of the results. Results of the study: the use in the greenhouses of the Republic of Uzbekistan of innovative new generation greenhouses with energy-saving technologies will reduce energy consumption, save resources and reduce the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…where b c -average value of the width of the spatial layer for the development of the root system of cotton; s -standard deviation of the spatial layer width for the development of the cotton root system; с -tolerance for horizontal vibrations of the machine; t -disc thickness. Thus, it was found that the width of the support-lumpbreaking coil should be at least 60 cm [22].…”
Section: Theoretical Justification Of Structural Elements Of Support-lump-breaking Coilmentioning
confidence: 99%
“…where b c -average value of the width of the spatial layer for the development of the root system of cotton; s -standard deviation of the spatial layer width for the development of the cotton root system; с -tolerance for horizontal vibrations of the machine; t -disc thickness. Thus, it was found that the width of the support-lumpbreaking coil should be at least 60 cm [22].…”
Section: Theoretical Justification Of Structural Elements Of Support-lump-breaking Coilmentioning
confidence: 99%
“…In particular, by the Decree of the President dated November 28, 2008, on the program of measures to support enterprises of the real sector of the economy, ensuring their stable operation and increasing export potential and the Decree of the President dated January 26, 2009, No. PP-1047 on additional measures to expand production food products and saturation of the domestic market, make it possible to systematically solve the problems of improving the living standards of the population and providing them with food products [20].…”
Section: Resultsmentioning
confidence: 99%
“…Methodological support is proposed to be built on the basis of individual elements of the "Pattern" method, which will identify asymmetry in the digital development of the regions of the Fergana Valley of the district and will indicate the presence of regional competitive advantages for the introduction of digital technologies. Such an analysis is carried out in relation to the economy as a whole, and not to individual sectors, since at this stage it is important to establish the general level of digitalization of the economy and the development of digital culture, which is expressed in systematic management decision-making based on the collection of a large amount of data using computer technology [9,10]. An important aspect of the study at this stage is also to identify the degree of digital inequality between different regions.…”
Section: Solution Of the Problemmentioning
confidence: 99%